Перамовы Сапегаў з пасламі рэспубліканцаў у Варшаве летам 1698 г - Vitko, Dmitry (Przegląd Środkowo-Wschodni, 2023)
An article devoted to a hitherto little-known attempt to peacefully end a great conflict, which went down in history as the civil war in the Grand Duchy of Lithuania (1696–1702). The causes of the conflict have not yet been fully explored. According to the author, they were best revealed during negotiations between the warring parties. The materials of the discussed negotiations provide the opportunity to trace mutual grievances, and based on how the conditions changed, we can deduce to what extent the parties actually sought to conclude a lasting settlement. The discrepancies concerned primarily the size and payment of the army, fiscal abuses and some other issues. Negotiations lasted from June 30 to July 22, 1698, under the auspices of King August II and some senators of the Commonwealth, and resulted in a settlement between the Sapiehas and the Republican deputies, who acted without the necessary powers, hoping for a future confirmation of the agreement. Under these conditions, the agreement did not resolve all the contentious issues, and partly even deepened them by increasing the number of troops and the remuneration of hetmans. The leading republicans remaining in the Grand Duchy rejected it and began preparations for a mobilization of nobility. In this way, instead of appeasing the conflict, it exacerbated it.